Kharijites In Khorasan (Based On History Of Sistan’s Materials) - Azimova Iroda Khomidjon kizi (Western European Studies, 2024)
The years of the rule of the Arab caliphate in Central Asia were difficult because of the foreign movement that was active in these areas. In this article, the history of foreign scholars against the caliphate and its viceroys in Khorasan and Movarounnahr is analyzed by foreign scientists, scientific research conducted during the years of the Russian Empire, the Soviet era, and the years of independence
Keywords: Orientalists of the Russian Empire; English scholars; Khurasan